(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
The basic enzyme in estradiol synthesis is, Aromatase, it is encoded by the gene called CYP19A1. Given the importance of estrogen in the development of Breast cancer risk, we studyt genetic polymorphisms in the CYP19A1 gene the, including rs10046, in a group of 45 patient women in Kerbala province, Iraq. Our aim to investigate CYP19AI polymorphism its impact on patients of Breast cancer in Iraqi women. We found in our study, that in Iraqi postmenopausal women,( rs10046) single nucleotides and polymorphism (SNPs) was prognostic of different levels of estrone and Estradiol. Depending on the BMI scale reveals 22.25% with the breast cancer group in Comparison with 30% of healthy women. In case of BMI with( 20-24) in the breast cancer group were 22.2% compared with the healthy group 20%., While BMI of >24 we found 33.4% in case of Breast cancer affected group in comparison with 20% of the unaffected group (Healthy). While in case of BMI >30 there were 22.2% in case of the Breast cancer group in comparison with 30% of unaffected (healthy) group. The molecular analysis of CYP19 gene ,reveals that A allele frequency was (0.6333) and G allele (0.3667) upon that, we found that the number of patients which have had breast cancer were 28 and 17 ,respectively. In summary, our data show that polymorphisms in the CYP19A1 gene may contribute to Breast carcinogenesis in Iraqi women.